The impact of fixed and variable costs on household car ownership - Gerard de Jong; Marco Kouwenhoven; Karst Geurs; Pietro Bucci; Jan Gerrit Tuinenga (Journal of Choice Modelling, 2009)
Car purchase taxes in The Netherlands are among the highest in the EU. The Dutch government plans to gradually replace car purchase and ownership taxes by a national road user charging system (kilometre charge) in the period 2012 to 2016. As a result, new and second hand car prices in the Netherlands will drop up to 30%. Relatively little research has been conducted on the impacts of such large price changes on car ownership. Reduced car prices are likely to lead to an increase in car ownership. But consumers could also refrain from buying extra cars when they consider the extra operating costs resulting from the kilometre charge. This paper presents one of the few empirical studies to examine the effects of both (large) fixed and variable car cost changes on both car ownership and use. An internet survey among Dutch households was designed and conducted including stated intentions and stated preference experiments. We investigated whether households react more to present one-off fixed costs than to recurrent variable costs, for various specifications of car costs. Model analysis was conducted to derive fixed and variable price elasticities for private car ownership and effects of the kilometre charge. The study shows in their car purchase decisions, households react more strongly to a change in euro per year in fixed car costs than to a euro per year in variable car costs. Abolishing the Dutch car purchase tax while at the same time introducing a kilometre charge will lead to 2% rise in car ownership on the short to medium run (1-5 years).
Keywords: 330; road pricing; car ownership; car use; discrete choice models; fixed and variable car costs